Social-Economic and Children’s Nutritional Status in Bengkulu Province - Sofais, Danur Azissah Roesliana; Rustandi, Handi; Suyanto, Jipri; Hidayat, Yance (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the factors related to the nutritional status of children in Bengkulu Province due to COVID-19 that affect economic conditions and make the healthy situation worse than before, especially child nutrition. The method used is a cross-sectional study conducted through an online questionnaire. The results of this study indicate that the factors that are significantly related to the nutritional status of children are; financially inadequate (AOR = 2.32; 95% CI: 1.50 to 3.60, P<0.0001), employed (AOR = 3.03; 95% CI: 193 to 4.76, P< 0.0001), living in urban areas (AOR = 1.59; 95% CI: 1.03 – 2.43, P: 0.034), local ethnicity (AOR = 1.72; 95% CI: 1.11 to 2, 68, P: 0.016) and low-income family support (AOR = 2.10; 95% CI: 1.34 to 3.28 < P<0.0001). In conclusion, financial condition, employment status, place, ethnicity, and family are related to the nutritional status of children in Bengkulu Province. Keywords: Financial Condition, Employment, Children's Nutritional Status